Human resource capabilities and their role in achieving organizational agility - Mohammed Hammadi // Zaid Salah Al- Dhalemi /Sahar Abbas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current research adopted revealing the role of human resources capabilities as an independent variable in achieving organizational agility as a dependent variable at the University of Maysan , as well as determining the type and nature of the relationship between these variables. And by defining the relationships of these variables as a problem that requires discovering solutions to it. This problem has resulted in a set of questions, which represent the main problem of the research, the most important of which is what is the role of human resources capabilities in achieving organizational agility at the university, the research sample. Achieving organizational agility for the university. The sample consisted of (166) administrators who held an administrative position at the university. The research relied on a number of statistical methods, tools, such as percentage, arithmetic mean and frequencies, as well as the adoption of test 2, normal distribution and structural stability according